An adaptive control algorithm for smart base isolation systems based on seismic early warning system. (April 2021) - Mohebbi, Mohtasham; Dadkhah, Hamed
Abstract: The common control strategy of smart base isolation composed of a low-damping rubber bearing and a magneto-rheological (MR) damper is to use MR damper in semi-active form. One drawback of this strategy is increasing the acceleration of isolated structure due to adding MR damper, especially under low-intensity earthquakes. This paper proposes a new adaptive-passive control approach for smart base isolation system. In this approach, MR damper performs in passive form while its behaviour is adjusted proportionally to intensity of the incoming earthquake which can be provided by a seismic early warning system (SEWS). For comparison purposes, hybrid control system has been also designed using the common control strategy in semi-active form. Because of the lack of high accuracy of SEWS in predicting the earthquake intensity, the performance of proposed control approach has been evaluated for an error of 20% in the estimated earthquake intensity. Evaluation of the performance of these control strategies under testing earthquake records shows that adaptive-passive control algorithm works better than semi-active control algorithm in controlling the seismic response of structure and the proposed control algorithm has effective performance under a wide range of earthquake intensities.